Complementary and Alternative Medicine (CAM) Use in Insomnia: Current Update on Knowledge, Attitude, and Perception among the Community in Malaysia - Siti Nur Afza Atirah Zahari; Syarifah Syamimi Putri Adiba Syed Putera; Zakiah Noordin (Asian Journal of Medicine & Health Sciences, 2022)
Background: Statistics have shown that 10-30% of adults have chronic insomnia, while 9 of 10 Malaysian have insomnia. Complementary and alternative medicine (CAM) is a well-known non-pharmacological intervention for insomnia. This study aims to evaluate the current update on knowledge, attitude, and perception (KAP) toward CAM therapy use in insomnia among the community in Malaysia. Methods: A self-administered, face-validated online questionnaire was distributed among 396 participants aged 18 years and above, recruited using convenience sampling between January and May 2022. The questionnaire consists of five sections: demographic, pattern usage of CAM therapy, knowledge, attitude, and perception of CAM therapy for insomnia. Sections 1 and 2 consist of multiple-choice questions, while each KAP part comprises 5-6 items of Likert scale questions. The overall score for each KAP section is calculated, and the level is classified by using Bloom’s cut-off point. Descriptive statistics were performed using SPSS version 22, and the data was presented in frequency and percentage. Results: Most of the respondents were single (81.3%), female (68.9%) university students (74%) with bachelor’s degrees (63.4%). Most respondents have never experienced insomnia (58.3%) and thus never practiced CAM therapy for insomnia (82.3%). Music-based intervention (n=36) and fixed sleeping patterns (n=55) are some reported CAM therapy practiced by insomniac respondents. Results also showed that participants have a positive perception (53.8%) and good knowledge (61.6%) of CAM therapy and insomnia but a moderate attitude (50.3%) toward CAM therapy for insomnia. Conclusion: The study findings revealed that the use of CAM therapy was not prevalent. Results also showed that participants had good knowledge of CAM therapy for insomnia. However, the researchers are unable to generalise the results of the survey to the population as a whole. Further research will require a larger sample size.